Corrigendum to "Climate reconstruction from pollen and δ13C records using inverse vegetation modeling – Implication for past and future climates" published in Clim. Past, 5, 147–156, 2009 - J. Guiot; C. Hatté; D.-D. Rousseau (Climate of the Past, 2010)
No abstract available.